Ethical Host, Prudent Host. Can You Steal from a Thief? - Rotengruber, Przemysław (Journal of Applied Cultural Studies, 2015)
Two parallel problems come under close scrutiny in my paper. First of them concerns the question whether victims of a (politically or economically) stronger thief are ethically entitled to steal their property in revenge? I argue that this kind of theft could be seen as a hidden form of protection because the symbolic relation between the first aggressor and his victim is extremely unequal. An ordinary man usually has no public means to oppose corporation or political institution. He has then to decide whether he chooses ethical perfection, which would stop him from doing anything; or he is ready, by himself, to inflict punishment on an (institutionalized) thief. The other problem concerns the consequences of the acceptance of ‘the balancing strategy.’ The case of modern state shows how hidden fighting against a stronger thief brings about opposite results. On one hand, an unfair political institution is deprived of its rights. But, on the other hand, the insubordinate citizen, who plays the part of the only owner of the criterion of fairness, destroys the rules of common life.